2015
DOI: 10.1016/j.ajog.2015.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Blood volume determination in obese and normal-weight gravidas: the hydroxyethyl starch method

Abstract: Objective The impact of obesity on maternal blood volume in pregnancy has not been reported. We compared the blood volumes of obese and normal weight gravidas using a validated Hydroxyethyl Starch (HES) dilution technique for blood volume estimation. Study Design Blood volumes were estimated in 30 normal weight (pregravid body mass index; BMI < 25 kg/ m2) and 30 obese (pregravid BMI > 35 kg/m2) gravidas after 34 weeks gestation using a modified HES dilution technique. Blood samples obtained before and 10 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 40 publications
2
27
1
1
Order By: Relevance
“…However, because fat mass is relatively underperfused compared with lean mass, the relation is curvilinear rather than linear, which results in estimates of 29-45 mL/kg in obese nonpregnant women (Table 1) (36,38,40). Plasma volume expansion in obese pregnant women remains understudied, although our recent publication suggests that it follows a similar trend to that in obese nonpregnant women (39). Investigation of abnormalities in plasma volume expansion in various disease states of pregnancy has also been limited, although some studies that were performed in pre-eclamptic patients have provided the basis for our understanding of this condition as one of volume contraction with decreased plasma volume estimates in pre-eclamptic women compared with in healthy and hypertensive controls (41).…”
Section: Smentioning
confidence: 92%
“…However, because fat mass is relatively underperfused compared with lean mass, the relation is curvilinear rather than linear, which results in estimates of 29-45 mL/kg in obese nonpregnant women (Table 1) (36,38,40). Plasma volume expansion in obese pregnant women remains understudied, although our recent publication suggests that it follows a similar trend to that in obese nonpregnant women (39). Investigation of abnormalities in plasma volume expansion in various disease states of pregnancy has also been limited, although some studies that were performed in pre-eclamptic patients have provided the basis for our understanding of this condition as one of volume contraction with decreased plasma volume estimates in pre-eclamptic women compared with in healthy and hypertensive controls (41).…”
Section: Smentioning
confidence: 92%
“…Often, the hematological parameters are usually normalized to body weight (BW) or body surface area (BSA) [5,6,24,30,34,62,64,75]. Therefore, obese individuals show lower BV to body weight after weight loss or in comparison to non-obese individuals [3,27,40,72]. The BSA has no physiological relationship to BV [18,44].…”
Section: Introductionmentioning
confidence: 99%
“…Given that body composition varies as a function of total bodyweight, optimising dosing in this population requires the identification of size descriptors, such as adjusted bodyweight, that share a quantitative relationship with changes in pharmacokinetics and associated pharmacological activity. When it comes to intravenous iron, it has been previously demonstrated that pregnant women who are overweight or obese have a greater total blood volume, which in turn would require a greater amount of iron to increase haemoglobin concentration relative to an individual of ideal bodyweight and a lower total blood volume.…”
Section: Discussionmentioning
confidence: 99%